Enhanced Klebsiella pneumoniae carbapenemase (KPC) expression from a novel Tn4401 deletion - Cheruvanky, A; Stoesser, N; Sheppard, A; Crook, D; Hoffman, P; Weddle, E; Carroll, J; Sifri, C; Chai, W; Barry, K; Ramakrishnan, G; Mathers, A (American Society for Microbiology, 2017)
The Klebsiella pneumoniae carbapenemase gene (blaKPC) is typically located within the mobile transposon Tn4401 Enhanced KPC expression has been associated with deletions in the putative promoter region upstream of blaKPC Illumina sequences from blaKPC-positive clinical isolates from a single institution were mapped to a Tn4401b reference sequence, which carries no deletions. The novel isoform Tn4401h (188bp deletion [lsqb]between istB and blaKPC[rsqb]) was present in 14% (39/281) clinical isolates. MICs for Escherichia coli strains containing plasmids with Tn4401a and Tn4401h were more resistant to meropenem (≥16, ≥16), ertapenem (≥8, 4) and cefepime (≥64, 4) than E. coli strains with Tn4401b (0.5, ≤0.5, ≤1). Quantitative RT-PCR demonstrated that Tn4401a had a 16-fold and Tn4401h a 4-fold increase in blaKPC mRNA levels compared to the reference Tn4401b. A lacZ reporter plasmid was used to test the activity of the promoter regions from the different variants and showed that the Tn4401a and Tn4401h promoter sequences generated higher β-galactosidase activity than the corresponding Tn4401b sequence. Further dissection of the promoter region demonstrated that putative promoter P1 was not functional. Activity of the isolated promoter P2 was greatly enhanced by inclusion of the P1-P2 intervening sequence. These studies indicate that gene expression could be an important consideration in understanding resistance phenotypes predicted by genetic signatures in the context of sequencing-based rapid diagnostics.